Assessment of the level of knowledge about health behaviors and puerperium of various social groups in the Świętokrzyskie Voivodeship during the Covid-19 pandemic - Anna Zwierzyńska; Jakub Gruszka; Karol Urbańczyk; Karolina Detka; Olga Adamczyk-Gruszka (Kazimierz Wielki University, 2022)
Introduction The puerperium is a period in a woman's life after childbirth, during which systemic changes occur. The woman's body returns to its pre-pregnancy condition. It lasts about 6 weeks. Having a baby and placenta causes changes in the concentration of pregnancy hormones, fluctuations that can negatively affect the behavior of women. In addition, the Covid-19 pandemic may interfere with the clinical condition of the pregnant woman, causing her mental health to deteriorate. Aim of the study: The aim of the study was the assessment of the level of knowledge about health behaviors and puerperium of various social groups in the Świętokrzyskie Voivodeship during the Covid-19 pandemic. Material and methods             The survey covered 603 respondents from the Świętokrzyskie Voivodeship from February to April 2021. 18 subjects were excluded from the study due to incomplete completion of the questionnaire. Ultimately, the analysis was conducted on the data of 584 respondents. The analyzes included women and men aged 19-45, who were divided into four groups. The first group included 130 obstetricians, the second 86 midwives, the third 50 teachers, and the fourth 318 students of the JKU. The Bioethics Committee of the JKU approved the study. Statistical analysis was performer. Results The respondents' knowledge about puerperium was 78.6%. Midwives had the most information, while obstetricians had the least. Participants in all 4 groups have a satisfactory level of knowledge about the duration of the puerperium, the principles of prophylaxis and hygiene in puerperium and feeding the newborn. The respondents obtain their knowledge from books and magazines.